Edible Film Based on Whey-Chia Seed: Physical Characterization with Addition of Different Plasticizers - Fahrullah Fahrullah; Djoko Kisworo; Azhary Noersidiq (Postgraduate, University of Mataram, 2023)
Edible film is a biodegradable packaging that can be an alternative as a food packaging material so as to reduce environmental damage and still have the function of maintaining the shelf life, quality and safety of food products. The aim of this research was to determine the effect of using different percentage of whey-chia seed and plasticizer type on the characteristics of films. This research used a completely randomized factorial design consisting of Factor A: percentage of whey-chia seed (A1= 1:0.5; A2= 1:0.75 and A3= 1:1) and Factor B: type of plasticizer (B1= sorbitol; B2= glycerol and B3= PEG). The interaction between of whey-chia seed and different types of plasticizer did not show a significant effect (p>0.05) on the characteristics of films, but the factor of whey-chia seed gave an effect on the thickness and gelation time of the films and the factor of different types of plasticizer too gave a significant effect (p<0.01) on the water vapor transmission rate (WVTR) value. The findings suggest that the incorporation of chia seed concentration with distinct plasticizers could enhance the physical properties of whey-based edible film. The use of percentage of whey-chia seed 1:1 with glycerol is the best treatment.